2012
DOI: 10.1128/jvi.05425-11
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of the Human RAD51 Nucleofilament Restricts HIV-1 Integration In Vitro and in Infected Cells

Abstract: ]. DNA-damaging agents, such as ionizing radiation and chemical compounds generating replication-blocking lesions like cis-platinum, also cause DSBs. Retroviral integration involving a cut of the genomic DNA can also be considered a potentially mutagenic event. The cellular DNA repair machinery could thus be required either for cell defense against viral infection or, inversely, for the stable integration of the viral genome. Since these machineries are not completely defined at present, they require better ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 44 publications
0
41
0
Order By: Relevance
“…For example, the cellular double-strand break repair proteins Rad51 (Cosnefroy et al, 2012; Desfarges et al, 2006), Ku (Zheng et al, 2011), and Rad18 (Mulder et al, 2002) have all been reported to interact with IN and may play a role in repairing the gaps in retroviral DNA integration intermediates to complete the creation of provirus (Yoder and Bushman, 2000). …”
Section: Discussionmentioning
confidence: 99%
“…For example, the cellular double-strand break repair proteins Rad51 (Cosnefroy et al, 2012; Desfarges et al, 2006), Ku (Zheng et al, 2011), and Rad18 (Mulder et al, 2002) have all been reported to interact with IN and may play a role in repairing the gaps in retroviral DNA integration intermediates to complete the creation of provirus (Yoder and Bushman, 2000). …”
Section: Discussionmentioning
confidence: 99%
“…γH2AX is an effector that modifies and makes accessible the structure of chromatin domains at the lesion sites [11,12], ultimately acting as a catalyst for the recruitment of the necessary cell cycle checkpoint and DNA repair factors [13]. Rad51 is the central enzymatic component of the mechanism that ensures homologous recombination and error-free repair of DSBs [14]. Collectively, the present data reveal the occurrence of DSBs and the activation of a repair response in human oocytes, suggesting novel aspects of the context that dictate success or failure of meiotic resumption.…”
Section: Introductionmentioning
confidence: 99%
“…This event triggers a complex cellular response that is directed to preserve the integrity of the host genome, as well as its chromatin architecture. This complex cellular response includes DNA damage repair and chromatin remodeling (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%